2012
DOI: 10.2176/nmc.52.603
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular Intraparenchymal Schwannoma

Abstract: A 60-year-old male presented with a rare case of periventricular schwannoma. Imaging studies revealed a partially calcified, well-enhanced tumor in the periventricular area of the left frontal horn. The preoperative diagnosis was low grade glioma, but postoperative pathological findings revealed that the tumor was schwannoma. Most intraparenchymal schwannomas are benign, so total extirpation is usually curative. However, this uncommon neoplasm is difficult to distinguish from mimics, especially low grade gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…They were reported to originate from the ventricular and periventricular structures. They have also been described in the cerebellar hemispheres,vermis and brain stem [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were reported to originate from the ventricular and periventricular structures. They have also been described in the cerebellar hemispheres,vermis and brain stem [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khoo HM et al reported that calcification was noted in 29%, cyst formation in 68% and peritumoral edema in 87.5% of the cases. These characteristics appear to be more frequent in intracerebral schwannomas than in acoustic neurinomas and peripheral schwannomas [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial schwannomas (ICS) usually arise from the vestibular portion of the eighth cranial nerve, less commonly from other cranial nerves including rare cases of olfactory and optic nerve schwannomas, and account for $8% of all primary intracranial tumors in adults. [1][2][3] Only a few case reports unrelated to cranial nerve intraparenchymal schwannomas are available since 1966 when the first case was described by Gibson et al [4][5][6][7][8][9][10] ICS constitutes $0.8% of all intracranial nerve sheath tumors. 11 In some cases, an associated neurofibromatosis (NF) was found.…”
Section: Introductionmentioning
confidence: 99%
“…15 Preoperative differential diagnoses include pilocytic astrocytoma, pleomorphic xanthoastrocytoma, ganglioglioma, meningioma, and glioblastoma. 10,16 Therefore, the primary treatment modality is often open surgery to gain histopathological verification and to select the right treatment modality.…”
Section: Introductionmentioning
confidence: 99%